Protecting the poor against health related financial burden: assessment of the legal-institutional framework in Egypt - Abd El Mogeith, Omkolthoum EL-Sayed (AUC Knowledge Fountain, 2014)
Egypt is ranked 113 out of 187 countries on the UNDP human development index, with about 40% of population living below the international poverty line. This research is intended to assess how the state is providing a social protection policies/ systems in order to protect disadvantage citizens in healthcare service provision sector. Measuring healthcare coverage and protection against financial risks answers the main research question which is “To what extent does the legal-institutional framework of the Egyptian governmental healthcare system(s) protect the poor from the health-related financial burden? The interventions that are subject to the study are Health Insurance (HIO), Payment on the Expense of the State (PTES) and Family Health Fund (FHF). The draft Social Health Insurance Law was also subject to the study. The researcher found that the draft Social Health Insurance Law provides good protection against financial risks associated with catastrophic health expenditures and Out-Of-Pocket (OOP) health expenditures. On the other hand, FHF offers the best program providing universal health coverage for both Millennium Development Goals (MDGs) related diseases and Critical Conditions and Injuries (CCIs) related illness comparing to other programs. Formularization of unified framework of those systems in order to integrate together along with clearly determining the roles of each system are the main policy recommendations of this study.